GAMBARAN STRES AKADEMIK PADA MAHASISWA BARU PRODI KEPERAWATAN UNIVERSITAS TANJUNGPURA PONTIANAK TAHUN AJARAN 2022 "“ 2023 - Lettia Vania, Maria Audrey; Maulana, M. Ali; Rahmawati, Nadia (Tanjungpura Journal of Nursing Practice and Education, 2024)
Background : New students will experience a transition period which can cause stress. If you are unable to adapt, it is likely that the individual will experience mental health problems and even experience academic stress. Academic stress is a condition that arises due to pressure to achieve academic achievement so that students feel burdened. High levels of stress not only disrupt the learning process, but also affect emotional, psychological aspects and even health problems. Method : Using quantitative research with descriptive analysis observational research design. Using a total sampling technique with a total of 97 Untan nursing students class of 2022 as research. subjects. The response rate was 94%. Face-to-face data collection and using the ESSA questionnaire. The statistical analysis test in this study used a univariate analysis test. Results : The results of univariate analysis were 2.2% (mild academic stress), 48.4% (moderate academic stress) and 49.5% (severe academic stress). The majority experienced academic stress based on characteristics, age 18 years 22.0% (moderate stress level), female gender 22.0% (severe stress level), Malay ethnicity 23.1% (severe stress level). Conclusion : There is academic stress among new students of the Tanjungpura University Nursing Study Program class of 2022. The majority of respondents in this study experienced severe academic stress.Keywords : Nursing, Students, Adolescents, Stress.